Efficacy of Soy Milk and Moringa Jelly Drink as a Nutritional Supplement for Enhancing Hemoglobin Levels in Postpartum Mothers - Aris Prastyoningsih; Frieda Ani Noor; Amrina Nur Rohmah; Dewi Kusumawati (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2026)
Background: Postpartum anemia is a condition with hemoglobin (Hb) levels <12 g/dL, which has a serious impact on the health of mothers and babies, increasing the risk of complications such as infection, postpartum hemorrhage, impaired breast milk production, anemia in infants, and delayed growth and development. Soy milk is a plant-based nutrient source rich in protein, iron, carbohydrates, healthy fats, fiber, and isoflavones, which play a role in hemoglobin synthesis and iron absorption. Moringa (Moringa oleifera) leaf extract also contains iron, vitamin C, protein, essential amino acids, as well as vitamin B complex and folate that support erythropoiesis.Methods: This study employed a one-group pretest posttest design, conducted at PMB Wulan from January to March 2025, involving a population of all postpartum women in the PMB Wulan work area (n = 20). The intervention was provided in the form of 250 ml of Soy Milk and Moringa Jelly Drink per day for 14 consecutive days.Results: The results showed a significant increase in Hb levels after the intervention, as determined by the Wilcoxon Signed Ranks Test (p = 0.003). The average Hb level increased from 9.505 g/dL to 10.525 g/dL, with an average change (delta) of 3.45. A total of 65% of respondents experienced an increase in Hb levels, 10% did not change, and 25% experienced a decrease.Conclusion: Consuming Soy Moringa Jelly Drink has the potential to be an alternative nutritional intervention to help increase hemoglobin levels.